Effect of taurine on glycaemic, lipid and inflammatory profile in individuals with type 2 diabetes: study protocol of a randomised trial. Issue 11 (14th June 2023) - Caletti, Greice; Cardoso, Monique Vargas; Scheffel, Rafael Selbach; Schaan, Beatriz D.; Gomez, Rosane; Bock, Patrícia Martins
Abstract: Type 2 diabetes mellitus (T2DM) is characterised by chronic hyperglycaemia. Despite the efficacy of conventional pharmacotherapy, some individuals do not reach glycaemic goals and require adjuvant therapies. Taurine, a semi-essential amino acid, decreases blood glucose and cholesterol levels in rodents and humans. However, glycated hemoglobin (HbA1c) has not been evaluated in randomised controlled trials after taurine treatment for more than 12 weeks. This study aims to evaluate the effect of taurine administration on glycaemic, lipid, inflammatory, anthropometric and dietary parameters in individuals with T2DM. A randomised, double-blind, placebo-controlled clinical trial will be conducted at the Clinical Research Center of a tertiary public hospital. Participants with T2DM ( n 94) will be recruited and randomised to receive 3 g of taurine or placebo, twice/day, orally, for 12 weeks. Blood samples will be collected before and after 12 weeks of treatment, when HbA1c, fasting glucose, insulin, albuminuria, creatinine, total cholesterol and fractions, triglycerides, C-reactive protein, TNF- α, IL 1, 4, 5, 6, 10 and 13 will be evaluated. Anthropometric parameters and 24-hour food recall will also be evaluated. The study will evaluate the effect of taurine treatment on biochemical and anthropometric parameters in individuals with T2DM. These results will guide the decision-making to indicate taurine treatment as an adjunct in individuals with T2DM who have not reached their glycaemic goal.